2015
DOI: 10.1002/srin.201400336
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Resistance Spot Welding of TWIP Steel Sheets

Abstract: A widespread usage of new advanced high strength TWIP steels in the automotive industry is conditional on proper assembly operations by welding. Therefore, the effects of the main important process parameters on the mechanical and microstructural properties of resistance spot welded TWIP sheets are examined here. The welding parameters used were the welding current, clamping force, and welding time. An L‐9(33) orthogonally array was used to design the experimental tests. The mechanical response of the welded j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…Yu et al [16] identified the RSW characteristics of 1 GPa grade TWIP steel. Spena et al [17] investigated the effects of the process parameters on the mechanical and microstructural properties of resistance spot-welded TWIP sheets and reported that an improper clamping force and weld current promoted excessive metal expulsions and the formation of welding defects in the weld spots. Yu et al [18] considered improvements to the weldability of 1-GPa grade TWIP steel, and found that a larger nugget size (NS) and higher tensile shear strength were obtained in constant power-control welding compared to constant current-control welding.…”
Section: Methodsmentioning
confidence: 99%
“…Yu et al [16] identified the RSW characteristics of 1 GPa grade TWIP steel. Spena et al [17] investigated the effects of the process parameters on the mechanical and microstructural properties of resistance spot-welded TWIP sheets and reported that an improper clamping force and weld current promoted excessive metal expulsions and the formation of welding defects in the weld spots. Yu et al [18] considered improvements to the weldability of 1-GPa grade TWIP steel, and found that a larger nugget size (NS) and higher tensile shear strength were obtained in constant power-control welding compared to constant current-control welding.…”
Section: Methodsmentioning
confidence: 99%
“…Russo Spena et al [24] reported that spot-welded 1.5 mm thickness TWIP steel joint failed in IF or PIF mode, while Saha et al [25] found that the 1.4 mm thickness TWIP steel joint always failed in IF mode.…”
mentioning
confidence: 99%
“…For instance, Zeytin et al [21] found a larger nugget diameter than the recommended value 4√h was needed to obtain the PF mode in terms of 1.0 mm thickness TWIP steel. Russo Spena et al [24] reported that spot-welded 1.5 mm thickness TWIP steel joint failed in IF or PIF mode, while Saha et al [25] found that the 1.4 mm thickness TWIP steel joint always failed in IF mode. Typical load-displacement curves of RSW joints under various welding current with constant welding time (20 cyc) are illustrated in Figure 12.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They reported a spot weld fusion zone (FZ) harder than the heat affected zone (HAZ), which facilitates the occurrence of ductile pullout failure (PF) mode, differing from the observed by Saha et al [6]. Russo Spena et al [10] and Kazdal Zeytin et al [11] on the other hand, observed softening in both HAZ and FZ when compared to the BM, indicating that softening mechanisms take part in the HAZ. The cited works, however, agree in that there is a distribution of mechanical properties throughout the weldment and such distribution in sensible to the welding parameters.…”
Section: /473mentioning
confidence: 86%